In vitro comparison of hydrolysis of different starches along the digestive tract of teleosts important for aquaculture - PAPOUTSOGLOU (Ε.Σ. ΠΑΠΟΥΤΣΟΓΛΟΥ) E. S.; LYNDON, A. R. (Journal of the Hellenic Veterinary Medical Society, 2017)
The in vitro hydrolysis of different starches (potato, rice, wheat, corn, sorghum), as well as an intermediate product of malting process (brewer’s spent grain), by blue tilapia, Oreochromis aureus, gilthead sea bream, Sparus aurata and European sea bass, Dicentrarchus labrax, were compared (total carbohydrase assay, 37° C, pH 7.6,4 hours incubation). Obtained results (significandy higher hydrolysis levels obtained for potato, rice and sorghum starch) suggest that starch source and associated properties (starch granule size, amylose content) and modifications applied may have significant difference on its digestion by fish digestive carbohydrases. Furthermore, the importance of brewer’s spent grain as a low-cost carbohydrate source and feed component, in relation to aglucosidase adaptive response to dietary carbohydrate, is also considered significant.